Microhabitat Utilisation of Endemic Lizard Calotes nigrilabris in the Grasslands of Horton Plains National Park, Sri Lanka, W.A.D. - Jayasekara, E.G.D.P.; Prabhath, M.C.; Mahaulpatha, W.A.D. (Department of Forestry and Environmental Science University of Sri Jayewardenepura, 2019)
The endemic endangered agamid lizard Calotes nigrilabris inhabits the grasslands of Horton Plains National Park (HPNP) and it is restricted to a few localities in the central highlands of Sri Lanka. In this study, the microhabitat utilisation of Calotes nigrilabris was investigated utilising line transects and quadrate method. The comparison of available microhabitat variables with occupied microhabitat variables revealed that there was a significant difference between some of the variables (Man-Whiteney U test, p<0.05) indicating that C. nigrilabris was selective in its microhabitat utilisation. Based on PCA analysis, amount and type of vegetation was the main determining factor of microhabitat preference of this species. Ulex sp. cover (PC1, 0.606) and Rhododendron sp. cover (PC2,-0.603) were significantly affecting the occupied microhabitat structure. Microhabitat utilisation varied in the temporal and spatial scales also indicating clear resource partitioning between different maturity stages. The results of this study indicate that C. nigrilabris actively selects and utilises the most suitable grassland microhabitats of HPNP and provide important insights for the conservation and management of the species as well as its natural habitat.
Keywords: Black-cheeked lizard, grassland habitat, resource partitioning, Agamidae, Ulex europaeus